Effect of Electrode Diameter and Current on Dissimilar Metal Welding (Stainless Steel - Galvanized Steel) in Bus Body Construction: Microstructure and Properties Evaluation - Suntari Suntari; Helmy Purwanto; Sri Mulyo Bondan Respati; Sugiarto Sugiarto; Zainal Abidin (Automotive Experiences, 2022)
This study evaluates the macrostructure, microstructure, hardness, and tensile strength in dissimilar metal welding applied to bus body construction. The process involved joining hollow stainless steel and galvanized steel at the dimensions of 80 x 40 x 3.2 mm through Gas Metal Arc Welding (GMAW). The current was varied at 90, 100, and 110 A while ER70S-6 electrodes with diameters of 0.8 and 1.0 mm were used. The results showed that electrode diameter and welding current affect the capping area, penetration depth, and hardness. Moreover, the formation of the widmasatten ferrite phase was increased and the coarse grain boundaries in the weld zone were detected. It was also observed that an increase in the diameter of the electrode and the welding current which indicates an increment in the heat reduced the rate of solidification and cooling. The average tensile strength for all the samples investigated was found to be lower than the value for the base metal. Therefore, further research is recommended to improve the tensile strength.